Pattern of admissions into the newborn unit of university of Uyo Teaching Hospital, Nigeria - U. Akpan, Mkpouto; Nyong, Eno E. (International Journal of Medical Research and Review, 2017)
Background: Neonatal conditions have been noted to contribute significantly to under-five mortality rate. Knowledge of its pattern in our environment will help in planning for improved health care delivery. Aim: To determine the morbidity and mortality patterns of patients admitted into the neonatal unit of the University of Uyo Teaching Hospital, Nigeria. Methods: A retrospective analysis of the medical records of patients admitted into the neonatal unit of the University of Uyo Teaching Hospital over a period of twelve months from 1st of January, 2011 to 31st of December, 2011 was carried out. Information extracted from the records included age at presentation, gender, duration of hospitalisation, main diagnosis, and outcome. Results: A total of 997 neonates were admitted during the period of review. The male to female ratio was 1.1:1 in favour of the males (529:468). Of these, the commonest diagnoses were: neonatal sepsis 253(25.38%), prematurity 188(18.86%), neonatal jaundice 181(18.15%) and birth asphyxia 137(13.74%). Mean duration of admission was9 days. The overall mortality rate was 12.9% with a male to female death ratio of1.3:1. Gender-related fatality rate was higher in males than females at 13.8% and 12.0% respectively. Majority (80.6%) of the deaths occur among the out-born while (43.4%) occur within 24 hours of admission. Conclusion: Most of the neonatal deaths were from preventable diseases. Good antenatal care is advocated for all pregnant women. This will help in screening, identification and timely referral of high risk pregnant women from primary health facilities to secondary and tertiary health facilities.